Clinical, immunological, and genetic landscape of common variable immunodeficiency in Morocco: a nationwide multicenter study - Allaoui, Abire; Moundir, Abderrahmane; Benhsaien, Ibtihal; Ailal, Fatima; Bakkouri, Jalila El; Echchilali, Khadija; Naitlho, Abdelhamid; Kabli, Hassan El; Bousfiha, Ahmed Aziz; Moudatir, Mina (Frontiers in Immunology, 2025)
BackgroundCommon Variable Immunodeficiency (CVID) is the most prevalent symptomatic inborn errors of immunity (IEI), characterized by impaired antibody production, recurrent infections, and immune dysregulation. While extensively studied in Western populations, data from North Africa remains scarce. This study provides the first comprehensive evaluation of the clinical, immunological, and genetic landscape of CVID in a Moroccan nationwide cohort.MethodsA multicenter, cross-sectional study was conducted across eight university hospitals in Morocco from 2019 to 2025. Sixty-one CVID patients were enrolled according to ESID (European society of immunodeficiency) and MENA (Middle-East and North Africa) guidelines. Clinical, immunological, and genetic data were analyzed. Whole-blood samples were processed for immunophenotyping, and a subset of patients underwent next-generation sequencing (NGS) targeting 474 inborn error of immunity (IEI)-associated genes.ResultsThe mean age at diagnosis was 25.9 (SD 18.7) years old, with a diagnostic delay of 6.91 (SD 8.82) years. The most frequent infectious complications were pulmonary infections (88.5%) and gastrointestinal infections (63.9%). Non-infectious complications were present in 49.2% of patients, with predominant features including lymphoproliferation (50.8%), autoimmune cytopenias (39.3%), and granulomatous disease (18%). Bronchiectasis was the most common pulmonary finding (44.3%). Genetic testing (n=25) revealed 19 pathogenic variants in 13 genes, including 14 novel variants, particularly LRBA, CTLA4, PIK3CD, NFKB1, VAV1, and TCF3. The phenotype-genotype correlation, based on clinical presentation, gene function, and multidisciplinary assessment, was strong in 52.6% of cases.ConclusionThis study provides Morocco’s first clinical and genetic landscape of CVID, highlighting a high prevalence of consanguinity-associated monogenic defects and a significant burden of infectious and immune dysregulatory complications. Our findings emphasize the need for early diagnosis, multidisciplinary management, and access to targeted therapies in non-Western settings. Further studies with functional validation of genetic variants are warranted to refine precision medicine approaches in CVID.